Effects of Preoperative Anxiety on Postoperative Delirium in Elderly Patients Undergoing Elective Orthopedic Surgery: A Prospective Observational Cohort Study - Ren A (Dove Medical Press, 2021)
Aolin Ren,1,* Na Zhang,1,* He Zhu,1 Kang Zhou,1 Yuan Cao,1 Jindong Liu1,2 1Department of Anesthesiology, Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China; 2Jiangsu Province Key Laboratory of Anesthesiology, Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jindong LiuDepartment of Anesthesiology, Affiliated Hospital of Xuzhou Medical University, Xuzhou Medical University, Huaihai West Road #99, Xuzhou 221000, People’s Republic of ChinaTel +86 10 8580-2333Email liujindong1818@163.comBackground: Postoperative delirium (POD) is common and has negative effects on elderly patients. There is a critical need to identify patients at high risk of POD so that providers can better offer targeted interventions in the preoperative and intraoperative periods. We aimed to characterize the prevalence of preoperative anxiety and investigate whether preoperative anxiety predicted the onset of POD in elderly patients undergoing elective orthopedic surgery.Methods: We conducted a prospective observational cohort study of elderly patients (aged 65 years or older) undergoing elective orthopedic surgery. Preoperative anxiety was assessed using the Hospital Anxiety and Depression Scale-Anxiety (HADS-A), with clinically significant values defined as HADS-A> 7. POD was diagnosed according to the Confusion Assessment Method (CAM) criteria on the 5 postoperative days. To determine the independent risk factors for POD, multivariable logistic regression was conducted, including those variables with a p-value < 0.05 at univariate analysis.Results: There were 263 patients included in the study. Seventy-three (27.8%) patients were diagnosed to be POD. Median duration of delirium was 2 days. Forty (15.2%) patients were assessed to experience preoperative anxiety. The occurrence of preoperative anxiety in total hip arthroplasty (THA), proximal femoral nail antirotation (PFNA), and total knee arthroplasty (TKA) was 12.5%, 16.1%, and 19.5%, respectively. Based on multivariable analysis, only age (odds ratio [OR]= 1.099, 95% Confidence Interval [CI]: 1.013– 1.192; P=0.023), Mini Mental State Examination (MMSE) (OR= 0.603, 95% CI: 0.432– 0.842; P=0.003) and preoperative anxiety (OR= 3.119, 95% CI: 1.144– 8.500; P=0.026) were independently associated with POD.Conclusion: In conclusion, the current study reveals that preoperative anxiety helps to predict the risk of POD in elderly patients undergoing elective orthopedic surgery. Relieving preoperative anxiety could be a new target for preventive interventions to reduce POD.Keywords: delirium, anxiety, orthopedic, risk factors